Efficacy of Seed Treatment Insecticides against Major Early Season Sucking Pests on Cotton in the Middle Awash, Afar Region, Ethiopia - Alemu, Zemedkun; Getahun, Sileshi; Seid, Nurhussein (Department of Agronomy and Horticulture, IPB University, 2025)
The sucking pest (whiteflies, aphids, cotton jassids, thrips, and cotton mealy bug) complex is a serious pest of cotton that causes a 22% decrease in yield. This research was carried out at Werer Agricultural Research Center in the Middle Awash of the Afar Region during the 2021 and 2022 cotton growing seasons to evaluate the efficacy of seed-dressing insecticides against an early-season sucking pest complex. Five treatments, including imidacloprid 70%, thiamethoxam 20% + metalaxyl - 20% + difenoconazole 2%, thiamethoxam 35% FS, thiamethoxam 25% WG, and untreated control, were evaluated in a randomized complete block design replicated four times. The results showed that the use of seed-dressing pesticides had a significant (P<0.05) influence on the populations of aphids, whiteflies, cotton jassids, and mealybugs. The thiamethoxam 25% WG was the most effective insecticide, with the highest pest reduction percentage and the lowest pest population resulting in significantly higher yield. This finding implies that thiamethoxam 25% WG can control early season sucking pests in cotton from emergence to six weeks in irrigated areas. Therefore, the use of thiamethoxam 25% WG as a seed dresser can be recommended as an option for controlling early season sucking pest complexes of cotton to prevent yield loss.